2011
DOI: 10.1073/pnas.1106467108
|View full text |Cite
|
Sign up to set email alerts
|

Integrin activation and internalization on soft ECM as a mechanism of induction of stem cell differentiation by ECM elasticity

Abstract: The mechanism by which ECM elasticity induces lineage specification of stem cells has not been clearly understood. Integrins are well-documented mechanosensors that are positioned at the beginning of the sensing pathway. By using an antibody specifically recognizing the active conformation of β1 integrin, we observed that β1 integrin activation in bone marrow mesenchymal stem cells (BMMSCs) was induced by soft substrate to a significantly greater degree than by stiff substrate. In contrast, however, the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
269
5
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 296 publications
(287 citation statements)
references
References 32 publications
8
269
5
5
Order By: Relevance
“…2D, panel i). The levels of activated integrin were determined using a ␤1 integrin antibody (clone HUTS-4) recognizing epitopes in the 355-425 region (hybrid domain), whose expression parallels the activity of ␤1 integrin (36). It is known that GPVI may form a dimer that has functional significance.…”
Section: Human Mks Express and Synthesize Ddr1-humanmentioning
confidence: 99%
“…2D, panel i). The levels of activated integrin were determined using a ␤1 integrin antibody (clone HUTS-4) recognizing epitopes in the 355-425 region (hybrid domain), whose expression parallels the activity of ␤1 integrin (36). It is known that GPVI may form a dimer that has functional significance.…”
Section: Human Mks Express and Synthesize Ddr1-humanmentioning
confidence: 99%
“…A similar phenomenon was also observed by Wei and colleagues, who saw an inhibition of β1-integrin activation and decreased phosphorylation of FAK on soft substrate. 45 In contrast, the study by Du et al 44 indicated that the reliance on specific ECM elasticity for cell lineage specificity was due to increased activation and internalization of β1 integrin on soft ECM substrates. The differences seen in integrin activation in these studies suggests that integrin regulation of the observed phenotypes may be cell type-dependent in addition to being influenced by elasticity and hence these factors should also be considered when examining the role of integrin signaling in vitro.…”
Section: B1 Integrin Regulates Tumorigenesis In 3d Contextsmentioning
confidence: 58%
“…Thus the elasticity of the growth environment may also be considered as a contributing factor to phenotypic differences observed in 2D vs. 3D assay conditions. Indeed, the importance of ECM elasticity has recently been noted for a variety of processes including transcription and replication, 41 and for the self-renewal and differentiation of stem cell populations in culture, [42][43][44] among others. Interestingly, the study by Kocgozlu et al 41 indicated that substrate rigidity affected both integrin and FAK activation, with a small window of optimal substrate elasticity for the activation of FAK to occur.…”
Section: B1 Integrin Regulates Tumorigenesis In 3d Contextsmentioning
confidence: 99%
“…The laminin-induced increase in proliferation was found to partially depend upon a contribution for the b1-integrin-binding site (especially a7b1 and a6b1) in the LG domains and substantially depend upon the polymerization activity of laminins. The latter effect may be an indirect one due in part to reduced laminins and other BM component receptor-ligands and possibly to an alteration of BM rigidity, a property recently found to be involved in integrin activity and turnover (Du et al, 2011).…”
Section: Discussionmentioning
confidence: 99%